Steady-state neutronic measurements and comprehensive numerical analysis for the BME training reactor. (1st June 2021) - Ványi, A.Sz.; Babcsány, B.; Böröczki, Z.I.; Horváth, A.; Hursin, M.; Szieberth, M.; Czifrus, Sz.
Abstract: This paper describes steady-state reactor physics measurements and calculations that were performed for the Training Reactor of Budapest University of Technology and Economics (BME TR) with the purpose of benchmarking. Based on the available geometry specifications and material compositions a model of BME TR was created with the well-validated, general-purpose Serpent 2 Monte Carlo code. Uncertain parameters (such as fuel density and control rod positions) were adjusted to related measurements. The Serpent 2 model was used for the generation of group constants, examining several homogenization schemes. Models were created in the PARCS diffusion code, the SPNDYN diffusion and SP3 code and the PARTISN discrete ordinates code. Various Monte Carlo and deterministic calculations were performed with the adjusted models and the results were then compared with actual measured data. The calculations and measurements show good agreement, this way the Serpent model was successfully validated, while the deterministic models make a good basis for more complex benchmarks in the future, such as transients with thermal–hydraulic feedback.